Primary granulocytic sarcoma of lip - A rare extramedullary presentation of myeloid leukemia - Tamojit Chaudhuri; Sayan Paul; Kirti Srivastava (Indian Journal of Medical and Paediatric Oncology)
A sixty year old male presented with a swelling in the upper lip. On cytopathology, the patient was diagnosed as a case of granulocytic sarcoma. His bone marrow examination was unremarkable. Patient was then treated by radiotherapy alone 30 Gray in 15 fractions and achieved complete response. Eighteen months after follow up the patient is absolutely normal. To our knowledge this is the first ever reported case of granulocytic sarcoma of lip.